Influence of performance level on exercise-induced arterial hypoxemia during prolonged and successive exercise in triathletes - Galy, O.; Hue, O.; Chamari, K.; Boussana, A.; Chaouachi, A.; Prefaut, C. (International Journal of Sports Physiology and Performance, 2008)
Purpose: To study the relationship between performance and exercise-induced arterial hypoxemia (EIAH), 5 internationally ranked (INT) and 8 regionally ranked (REG) triathletes performed cycle-run successions (CR) and control runs (R) in competition-like conditions: at ˜75% VO2max. Methods: Ventilatory parameters and oxyhemoglobin saturation (SpO2) data were collected continuously. Arteriolized partial pressure in O2 (PaO2) and alveolar ventilation (VA) were measured before and after cycling (CRcycle), the successive run (CRrun), and R. Pulmonary diffusing capacity (DLco) was measured at rest and 10 minutes post-CR. Training and short-distance triathlon data were collected. Results: INT showed significantly greater experience than REG in competition years (P > .05), training regimen (P > .05), and swimming (P > .05), and cycling (P > .05) volumes; running showed a trend (P < .06). Cycling, running, and total triathlon performances were significantly higher in INT than REG (P > .01). SpO2 during CR dropped significantly more in INT than in REG. Both groups showed significant inverse correlations between the magnitude of the SpO2 change from CRcycle to CRrun and the triathlon running time (r = -0.784; P < .05 and r = -0.699; P < .05; respectively). When compared with CRcycle, PaO2 significantly decreased and VA significantly increased after CRrun and R in both groups (P < .01). DLco significantly dropped between pre- and postexercise in CR and R with no between-group difference (P < .05). Conclusions: EIAH was aggravated in higher performers during simulated cycle-run segments, related to longer experience and heavier training regimens. Possibly, relative hypoventilation caused this aggravated EIAH in INT, although pulmonary diffusion limitation was observed in both groups. Beyond EIAH severity, the magnitude of SpO2 variations during the cycle-run transition may affect triathlon running performance.